2013
DOI: 10.1186/1475-2891-12-108
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between body composition and cardiovascular risk factors in young Australian men

Abstract: IntroductionCardiovascular (CV) disease is a leading cause of global mortality. Despite clear evidence of the coexistence of several risk factors in young people as children and an understanding of the importance of the health behaviors in controlling CV disease, there are limited data on the relationships between risk factors and CV disease in young people. Therefore further study is required.ObjectiveThis study aimed to investigate associations among body composition, health behaviors and CV risk factors in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…A study conducted with adolescents in Campina Grande (PB) showed an association between BMI and TC and its LDL fraction 6 . Santos et al 25 and Liberato et al 26 reported a negative correlation between HDL-c and BMI.…”
Section: Discussionmentioning
confidence: 96%
“…A study conducted with adolescents in Campina Grande (PB) showed an association between BMI and TC and its LDL fraction 6 . Santos et al 25 and Liberato et al 26 reported a negative correlation between HDL-c and BMI.…”
Section: Discussionmentioning
confidence: 96%
“…Regarding the relationship between anthropometric and health parameters, previous studies reported a clear relationship between body composition and the risk of developing cardiovascular diseases and type II diabetes [ 62 , 63 ]. In contrast, in the present study, although BMI, FAT, LBM, and AG were significantly correlated with all the health parameters analyzed except SPO2, these correlations were weak or moderate in the case of BMI, FAT, and AG, and weak in the case of LBM.…”
Section: Discussionmentioning
confidence: 99%
“…The greater the obesity level, the body fatness or the abdominal obesity the greater the risk of developing cardiovascular disease. Other risk factor of cardiovascular disease include physical inactivity, elevated psychosocial stress and inappropriate diet [4 ] .…”
Section: Introductionmentioning
confidence: 99%